Investigating The Use Of Contextual Teaching and Learning (CTL) In Teaching Speaking At The Second Year Of SMPn 3 Colomadu - Logislatif, Rendi Tyas (2012)
This research aims at finding out the implementation of Contextual Teaching and Learning in teaching speaking and to find strengths and weaknesses of teaching speaking in SMP N 3 Colomadu. The writer takes the English teacher and students of the second year as the subject of the study. In this research, the writer used the qualitative research for analyzing the data. To collect the data the writer uses observation, interview, and document. The data were analyzed by finding out the teaching procedures used by the teacher in teaching English using CTL method, comparing the result of interview with the situation in the class, making note about the activities in classroom, concluding the procedures used by the teacher are appropriate or not with the seven components in CTL, making conclusion based on the result of analysis and giving some suggestions. The result of the analysis shows that (1) there are three-phase techniques teaching learning process: pre-teaching, whilst teaching, and post teaching. There are seven components used by the teacher in teaching learning process: constructivism, inquiry, questioning, learning community, modeling, reflections, and authentic assessment. The teaching procedures used by the teacher are appropriate with components of CTL in giving material to the students. (2) There are three strengths of CTL: the students become more active and creative in teaching learning process, there is cooperation between students, and the teacher easy to teach the material. While the weaknesses of CTL are: The teacher finds difficulty for giving score to the students and managing of time.